Relief Astadikpalaka Candi Siwa Prambanan: Materialisasi Astabrata Penguasa Mataram Kuno - Rochman, Luthfan Nur; Munandar, Agus Aris (PURBAWIDYA, 2026)
This study examines the Astadikpalaka reliefs (the eight guardian deities of the cardinal directions) at the Siwa Temple of Prambanan as the materialization of the Astabrata political ideology during the reign of Rakai Pikatan (9th century CE). By applying Anthony Giddens' structuration theory as adapted in archaeology by Andreas G. Orphanides, this research analyzes the reliefs not as passive objects but as active components in the reproduction of power structures. Using a qualitative-interpretative approach, data were collected from iconographic studies, the Siwagrha inscription (856 CE), and Astabrata texts. The findings indicate that the Astadikpalaka reliefs represent the eight ideal kingly virtues of Astabrata while also functioning as a legitimizing medium that naturalizes Rakai Pikatan's authority through cosmic symbolism. This study concludes that Prambanan Temple served not only as a sacred site but also as a political instrument that reinforced the hegemony of the Ancient Mataram rulers.